The Conflicts of The Main Character Ken Carter in The Movie “Coach Carter” - Ida Bagus Gede Subawa Putra; I Nengah Sudipa; I Nyoman Aryawibawa (CV. Ulil Albab Corp, 2023)
This study analyzes the conflicts experienced by the main character Ken Carter in the movie